Plasma 25-hydroxyvitamin D concentrations in preterm infants receiving oral vitamin D supplements. Issue 2 (February 1981) - Robinson, M J; Merrett, A L; Tetlow, V A; Compston, J E
Abstract : Plasma 25-hydroxy-cholecalciferol (25-OHD) was measured serially in two groups of preterm infants receiving either 400 IU or 1000 IU oral vitamin D3 daily. All the babies were able to absorb and hydroxylate vitamin D3 adequately by 36 weeks' gestational age. The higher daily supplement had no advantage over the lower dose.